Students' Perceptions about Bullying Behavior - Intan Pratiwi; Daharnis Daharnis (Universitas Negeri Padang, 2019)
Bullying behavior is behavior that hurts someone repeatedly. Bullying behavior has several aspects, namely physical, verbal, relational, and sexual aspects. This research uses quantitative descriptive methods. The study population was 296 in SMP 35 Padang and a sample of 170 students were selected using the Stratified Random Sampling technique. The instrument used was a questionnaire in the form of a Semantic Differential scale.The research findings reveal that students' perceptions of bullying behavior in general students assume bullying behavior is strictly not allowed. Specifically, students' perceptions about bullying behavior from physical, verbal, relational, and sexual aspects are still students who are hesitant about bullying or not, even there are still students who consider bullying behavior to be allowed